Researching temporary migration and domestic and family violence - Segrave, Marie Therese (The borders of violence, 2025)
This chapter interrogates the methodological gaze adopted when researching violence against women via the analytical lens of border control, migration and temporariness. To do so, we offer a detailed account of the methodological approaches applied in the two studies that are brought together for this analysis. The chapter explores the ethics of researching victim-survivor experiences of domestic and family violence (DFV), the opportunities and limits of using case file research and interview-based approaches, and the reproduction of othering and/or exclusion and imposition of binaries of identity when researching migrant women's experiences of violence, DFV in particular. The discussion considers the value of both thick and thin approaches to data collection and of bringing complementary datasets together to deepen interrogation of the relationship between DFV and migration status. We argue that research can and does continue to reproduce inequality, and we note the ongoing challenges for feminist research into bordering practices and structural violence. We end the chapter with an elevation of the voices of women in the interview study, who articulated the value and impact of research participation. This speaks to one of the key objectives of this research: to bring into view the perspectives of women, who are often silenced in scholarship on DFV. Key to this book is also affirmation of the close connection between women's safety and advocacy to advance it, as well as the importance of scholarly interrogation of the conditions that sustain women's inequality.